Evaluation of The Implementation of Merdeka Curriculum Policy at SDN Menteng 02 Pagi - Basuki, Gayatri; Ahmad, Masduki; Zulaikha, Siti (Universitas Negeri Malang, 2024)
Abstract: On February 11, 2022, the Minister of Education, Culture, Research and Technology launched the Fifteenth Episode of Merdeka Belajar policy: Merdeka Curriculum and Merdeka Teaching Platform online, as an option for learning recovery. The Merdeka Curriculum focuses on student competence & character education, so the Merdeka Curriculum structure consists of two components, namely intracurricular learning and project learning through character education (Projek Penguatan Profil Pelajar Pancasila/P5). This study aims to understand the communication strategies, resources, attitudes of policy implementers and standard operating procedures (SOPs) carried out by policy makers to policy implementers (SDN Menteng 02 Pagi) in transmitting the implementation of the Merdeka Curriculum policy. The method chosen uses a qualitative approach with a descriptive evaluative method and refers to the policy from George C. Edwards III. The data collection techniques used are interviews, observation and documentation studies by performing data analysis techniques, data reduction, data display, and conclusion drawing. The result of the study is that the policy implemented in the Merdeka Curriculum in elementary schools aims to provide adequate facilities for innovative learning for students. With this policy, it can encourage the learning process in elementary schools to become more flexible or organized, because the principle of the Merdeka Curriculum itself requires students to master expertise in the fields they want in soft skills and hard skills. Keywords: Evaluation; Implementation; Merdeka Curriculum; Policy; Public School